Formalizing Feature Inheritance - Gregory Kobele; Lei Liu (Society for Computation in Linguistics, 2025)
Feature Inheritance is a prominent theoretical innovation in minimalist syntax, which takes it further from the formal framework of minimalist grammars, the best understood formalism for reasoning about minimalism. Feature inheritance involves movement targeting non-root positions, as well as simultaneous movement steps. This turns out to require a formally innocuous extension to minimalist grammars, leaving strong generative capacity and worst-case parsing complexity unchanged.
Keywords: minimalist grammars; minimalist syntax; feature inheritance; complexity